Bibliometric Analysis to A Future Research Direction on Agile Transformation - Sidik Darusulistyo; Dermawan Wibisono; Harimukti Wandebori; Santi Novani (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
Agile transformation has become increasingly popular as a management approach to improve performance, but there has been limited research on its direction. This study aims to advance knowledge on agile transformation to help companies become faster, more flexible, and more responsive. The study employs a bibliometric approach to analyze 116 "Agile Transformation" papers published in the Scopus database over the past 20 years. The findings indicate an increasing number of publications in recent years, with the United States, Finland, and Germany being the top countries. However, the research connections are not yet consolidated, as only 22 authors out of 282 have co-authored papers. The research has also been mainly focused on software development and IT companies, using case studies, grounded theory, and surveys. The study reveals that the major research hotspots in the agile transformation are agile transformation, software development, software design, agile methods, agile transition, and agile adoption. The grand theories emerging in the Agile Transformation revolution emphasize the importance of collaboration, communication, continuous improvement, and customer value. Overall, this study provides a comprehensive understanding of the current state of research on agile transformation and offers insights for future research. The findings highlight the need for greater research diversity beyond software development and IT companies and an opportunity to use action research and ethnography strategies to understand agile transformation. Ultimately, this study contributes to the advancement of knowledge on agile transformation and its role in improving organizational performance.